Modelling factors influencing early adopters purchase intention towards online music - Norazah Mohd Suki (IGI Publishing, 2011)
The Internet is an incredible technology, offering users a vast choice of new songs and catalogue that can be browsed, streamed or bought online. This paper aims to provide an explanation of factors influencing purchase intention of early adopters towards online music. An empirical survey was used to test the hypotheses. Data were collected from a total of 200 questionnaires distributed to early adopters of online music and were analysed using Structural Equation Modeling (SEM) via the Analysis of Moment Structure (AMOS 16) computer program. Results enumerate that perceived ease of use emerges as the important factor which affects perceived value among the respondents followed by perceived playfulness. Perceived value has the only significant impact on the purchase intentions towards online music. The paper rounds off with conclusions and an agenda for future research in this area.